Postnatal depression and its effects on child development: a review of evidence from low- and middle-income countries. - Parsons, C; Young, K; Rochat, T; Kringelbach, M; Stein, A (2012)
INTRODUCTION OR BACKGROUND: It is well established that postnatal depression (PND) is prevalent in high-income countries and is associated with negative personal, family and child developmental outcomes. SOURCES OF DATA: Here, studies on the prevalence of maternal PND in low- and middle-income countries are reviewed and a geographical prevalence map is presented. The impact of PND upon child outcomes is also reviewed. AREAS OF AGREEMENT: The available evidence suggests that rates of PND are substantial, and in many regions, are higher than those reported for high-income countries. An association between PND and adverse child developmental outcomes was identified in many of the countries examined. AREAS OF CONTROVERSY: Significant heterogeneity in prevalence rates and impact on child outcomes across studies means that the true extent of the disease burden is still unclear. AREAS TIMELY FOR DEVELOPING RESEARCH: Nonetheless, there is a compelling case for the implementation of interventions to reduce the impact of PND on the quality of the mother-infant relationship and improve child outcomes.